Growth performance, carcass quality, fresh belly characteristics, and commercial bacon slicing yields of growing-finishing pigs fed a subtherapeutic dose of an antibiotic, a natural antimicrobial, or not fed an antibiotic or antimicrobial. (February 2018) - Lowell, J.E.; Bohrer, B.M.; Wilson, K.B.; Overholt, M.F.; Harsh, B.N.; Stein, H.H.; Dilger, A.C.; Boler, D.D.
Abstract: The objective was to compare growth performance, belly characteristics, and bacon slicing yields of growing-finishing pigs fed a subtherapeutic dose of an antibiotic, a natural antimicrobial, or a diet containing no antibiotics or antimicrobials. Barrows and gilts (96 each, initial BW: 27.52 ± 3.98 kg) were housed in 48 pens (8 replications per treatment) in a 2 × 3 factorial randomized complete block design. Pens were assigned 1 of 3 diets: antibiotic free, oregano or tylosin phosphate. Pigs were slaughtered at an average BW of 127.31 ± 10.18 kg. There were no differences among dietary treatments for growth performance ( P ≥ 0.06), carcass cutability ( P ≥ 0.42), loin quality ( P ≥ 0.28), fresh belly dimensional characteristics ( P ≥ 0.11), IV ( P ≥ 0.87) or bacon processing characteristics ( P ≥ 0.07). Given the lack of differences in meat quality from pigs fed diets without antibiotics, the implementation of VFD in the United States should not result in changes in pork quality. Highlights: Subtherapeutic antibiotics can increase growth rate of pigs and alter carcass composition. Diets were formulated identically except diet 1 contained no additive (antibiotic free). There were no interactions between sex and dietary treatments. There were no dietary differences in LM quality, belly characteristics, fat quality, or bacon characteristics. Diets that did not contain dietary antimicrobials did not compromise carcass composition or meat quality.